2011
DOI: 10.1525/jer.2011.6.4.30
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Genetic Research Results: Reflections from Individuals with and without a Known Genetic Disorder

Abstract: In the debate about whether to return individual genetic results to research participants, consideration of the nature of results has taken precedence over contextual factors associated with different study designs and populations. We conducted in-depth interviews with 24 individuals who participated in a genotype-driven study of cystic fibrosis: 9 of the individuals had cystic fibrosis, 15 had participated as healthy volunteers, and all had gene variants of interest to the researchers. These interviews reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 18 publications
(34 reference statements)
3
66
0
Order By: Relevance
“…It has been suggested that these two populations may view their obligations to extended family members differently, given the inherent broader familial impact of inherited conditions versus that of typically isolated pediatric cancers. 21,22 We explore themes focused on parental attitudes toward (i) sharing of target and incidental findings discovered in the course of pediatric genomic research; (ii) responsibilities toward family members; (iii) acceptability of children participating in genomic research; Purpose: We describe parental attitudes toward the return of targeted and incidental genomic research results in the setting of highrisk pediatric cancer and inherited childhood diseases. …”
mentioning
confidence: 99%
“…It has been suggested that these two populations may view their obligations to extended family members differently, given the inherent broader familial impact of inherited conditions versus that of typically isolated pediatric cancers. 21,22 We explore themes focused on parental attitudes toward (i) sharing of target and incidental findings discovered in the course of pediatric genomic research; (ii) responsibilities toward family members; (iii) acceptability of children participating in genomic research; Purpose: We describe parental attitudes toward the return of targeted and incidental genomic research results in the setting of highrisk pediatric cancer and inherited childhood diseases. …”
mentioning
confidence: 99%
“…The Declaration, revised in Tokyo in 1975, in Venice in 1983, and again in Hong Kong in 1989, is a comprehensive international statement of the ethics of research involving human subjects. It sets out ethical guidelines for physicians engaged in both clinical and non-clinical biomedical research, and provides among its rules for informed consent of subjects and ethical review of the research protocol [10].…”
Section: International Declarations and Guidelines For Ethical Frameworkmentioning
confidence: 99%
“…Here the ethical principle of autonomy (the basis of informed consent in contemporary research) is pitched against the 'right not to know' and the principle of non-maleficence (the precept to do no harm) 1 . This central tension in RbG research (also termed Genotype Driven Recruitment (GDR)) has been identified [2][3][4] in studies involving biobanks and other repositories that include participants with genotypic data collection, including disease and tissue-based biobanks [5][6][7] , population-based biobanks 5 and collections based on health records or direct to consumer testing 8 .…”
Section: Introductionmentioning
confidence: 99%
“…While careful not to conflate the issues of return of clinically useful findings (incidental findings) with disclosure of genetic information through recruitment, these studies point to a range of cognate issues that bear consideration: the need to avoid participant anxiety if the genetic information -or re-contact itself -is unexpected 2,8 ; the possibility that even uncertain information may be important to participants 7 ; and the challenge that informational utility includes personal utility and personal meaning as well as clinical utility, especially where there is parental, familial or personal experience of disease [5][6][7]9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation